1993
DOI: 10.1159/000201029
|View full text |Cite
|
Sign up to set email alerts
|

Natural Course in Chronic Pancreatitis

Abstract: The natural course of the classical symptoms of chronic pancreatitis, i.e. pain, exocrine and endocrine pancreatic insufficiency, was followed up in 335 patients over a median of 9.8 years (mean 11.3 ± 8.3 years). Pain relief was not obtained in the majority of patients, even after a long-term observation of > 10 years, and severe excocrine/endocrine insufficiency, severe duct abnormalities and pancreatic calcifications developed. Alcohol abstinence failed to have a significant beneficial effect on pain. Pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
7

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(49 citation statements)
references
References 10 publications
1
41
0
7
Order By: Relevance
“…Moreover, the cumulative risk of pancreatic cancer increased distinctly, and 10 and 20 years after a diagnosis of CP, the risks were found to be 1.8 and 4%, respectively, in a multicenter study conducted by Lowenfels et al[ 24]. The incidence of associated pancreatic cancer was found to be 1.6% in a recent Japanese study[ 28], and the overall incidence of pancreatic cancer in our study was 3.1%, which is similar to several Western studies that reported a higher incidence of pancreatic cancer in CP [20, 26, 27]. Smoking is the most well-established risk factor of pancreatic cancer, and this risk appears to be independent of sex, country, or type of pancreatitis[ 25].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the cumulative risk of pancreatic cancer increased distinctly, and 10 and 20 years after a diagnosis of CP, the risks were found to be 1.8 and 4%, respectively, in a multicenter study conducted by Lowenfels et al[ 24]. The incidence of associated pancreatic cancer was found to be 1.6% in a recent Japanese study[ 28], and the overall incidence of pancreatic cancer in our study was 3.1%, which is similar to several Western studies that reported a higher incidence of pancreatic cancer in CP [20, 26, 27]. Smoking is the most well-established risk factor of pancreatic cancer, and this risk appears to be independent of sex, country, or type of pancreatitis[ 25].…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of pancreatic cancer during the course of CP has been reported to range from 1.1 to 3% in the West[ 20,22,23,24,25,26,27]. Moreover, the cumulative risk of pancreatic cancer increased distinctly, and 10 and 20 years after a diagnosis of CP, the risks were found to be 1.8 and 4%, respectively, in a multicenter study conducted by Lowenfels et al[ 24].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to chronic pancreatitis, where exocrine pancreatic insufficiency deteriorates within 6.5 years in more than 40% of the patients [24], exocrine pancreatic function, if initially normal or abnormal, does not change significantly in type-1 diabetes mellitus. If abnormal, exocrine pancreatic insufficiency is only mild to moderate and stays in this range.…”
Section: Discussionmentioning
confidence: 99%
“…Lankisch et al [22]showed that in patients with chronic pancreatitis the survival rate 10 years after conservative treatment was 80% for non- alcoholics and 65% for patients still consuming alcoholic beverages. Lowenfels et al [23]described a 10-year survival rate of 70%, whereby continuous nicotine and alcohol consumption influenced the prognosis of the patients negatively.…”
Section: Discussionmentioning
confidence: 99%